2014
DOI: 10.1063/1.4891734
|View full text |Cite
|
Sign up to set email alerts
|

Coplanar waveguide based ferromagnetic resonance in ultrathin film magnetic nanostructures: Impact of conducting layers

Abstract: We report broadband ferromagnetic resonance (FMR) measurements based on a coplanar waveguide (CPW) of ultrathin magnetic film structures that comprise in-plane/out-of-plane decoupled layers deposited on nonmagnetic buffer layers of various thickness or other buffer structures with a diverse sheet resistance. We show that the excitation of the fundamental mode can be substantially (up to 10 times) enhanced in the structures deposited on buffer layers with a low sheet resistance in comparison to the structures d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The microwave conductivity contribution to the stripline broadband ferromagnetic resonance (FMR) response of highly-conducting (metallic) magnetic multilayers and nanostructures of sub-skin-depth thicknesses has attracted significant attention in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It has been shown that these effects are important when the microwave magnetic field is incident on only one of the two surfaces of a planar metallic material (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The microwave conductivity contribution to the stripline broadband ferromagnetic resonance (FMR) response of highly-conducting (metallic) magnetic multilayers and nanostructures of sub-skin-depth thicknesses has attracted significant attention in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. It has been shown that these effects are important when the microwave magnetic field is incident on only one of the two surfaces of a planar metallic material (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As a simplification, the change in S-parameters with magnetic field ∆S 21 or ∆S 11 are also commonly used in the literature as a proportional mea-255 sure of the complex susceptibility [12,13,14,22 Both the lumped and distributed element models assume that the measurement device is perfectly calibrated and the probes are placed equidistant from the sample, i.e., the reference plane is deembedded to the edge of the sample [15]. In reality, 265 proper de-embedding of the sample is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The technique extends from previous work measuring the ferromagnetic resonance (FMR) of magnetic thin-films and other nanostructures by use of a combination of vector network analyzer (VNA) and coplanar waveguides (CPW), referred to in the 60 literature as VNA-FMR [12,13,14,15,16,17]. We compare the resonance spectra from cavitybased EPR and broadband on-wafer EPR using dilutions of ferumoxytol and TEMPO (2,2,6,6-tetramethylpiperidine 1-oxyl) in both frozen and dried states.…”
mentioning
confidence: 99%
“…Nevertheless, a reliable and authentic value of the permeability is very important for such applications. FMR based on a VNA and CPW has become a common experimental tool for studying magnetic films [3]. However, the necessity for an accurate and localized characterization of these materials in terms of electric and magnetic properties is still needed.…”
Section: Introductionmentioning
confidence: 99%